Navigating Educational Transformation: The Response of SMK DKV Nurul Qarnain to the Age of Artificial Intelligence and Policy Dynamics - Mohammad Fikri (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
Recent shifts in national education policy, particularly under the new government, have brought notable implications for vocational schools. Simultaneously, the rapid evolution of artificial intelligence (AI) continues to reshape teaching and learning practices across the country. SMK Desain Komunikasi Visual Nurul Qarnain, situated within a traditional Islamic boarding school, is one of the institutions facing the challenge of navigating these dual pressures. This research employed a qualitative approach, involving in-depth interviews, observations, and document analysis. The findings indicate that the school grapples with structural limitations, including limited access to digital resources and state policies that prioritize efficiency and market alignment. Nevertheless, the institution has begun adjusting its curriculum and teaching methods, integrating AI tools selectively to support student creativity. The study reveals the capacity of such schools to develop value-based forms of adaptation that align with local needs and offer insights for more inclusive and responsive educational policy design.